Alcoholics Anonymous and other mutual help organizations: Impact of a 45-minute didactic for primary care and categorical internal medicine residents. Issue 2 (3rd April 2017) - Marcovitz, David; Cristello, Julie V.; Kelly, John F.
ABSTRACT: Background : Substance use disorders (SUDs) are highly prevalent among primary care patients. One evidence-based, cost-effective referral option is ubiquitous mutual help organizations (MHOs) such as Alcoholics Anonymous (AA), Narcotics Anonymous (NA), and SMART Recovery; however, little is known about how to effectively increase trainee knowledge and confidence with these referrals. The primary aim of this study was to evaluate whether a single 45-minute combined lecture and role play–based didactic for primary care residents could enhance knowledge, improve attitudes, and bolster confidence in referring patients with addictions to community MHOs. Methods : The authors developed a 45-minute lecture and role play addressing the evidence for MHOs, their respective background/content, and how to make effective referrals. Participants were administered a brief survey of their MHO-related knowledge, attitudes, and confidence before and after the session to evaluate the didactic impact. Results : Participants were 55 primary care and categorical internal medicine residents divided among postgraduate year 1 (PGY1; 27.3%), PGY2 (38.2%), and PGY3 (34.5%). They had a mean age of 29 (SD = 2.62); 49% were female, 69% were Caucasian, and 78% reported some religious affiliation. Participants' subjective knowledge about MHOs increased significantly ( P < .001), as did their confidence in making referrals ( P < .001). Changes in participants' attitudes about the importance of MHOs in aiding successful addiction recovery approached significance ( P = .058). The proportion of participants with correct responses to each of 4 knowledge-based questions increased substantially. Conclusions : Primary care and internal medicine residents reported variable baseline knowledge of MHOs and confidence in making referrals, both of which were improved in response to a 45-minute didactic. Role play may be a useful supplementary tool in enhancing residents' knowledge and skill in treating patients with SUD.